Economic Wealth Creation and the Social Division of Labour Volume I: Institutions and Trust - Gilles, Robert P. (Springer International Publishing, 2018)
This textbook introduces and develops new tools to understand the recent economic crisis and how desirable economic policies can be adopted. Gilles provides new institutional concepts for wealth creation, such as network economies, which are based on the social division of labour. This volume investigates the formation of networks and hierarchical authority organisations, with a focus on the role of trust. Gilles also looks at the theory of growth and development, using real world examples and problem sets to put into practice. This title is suitable reading for undergraduate, MSc and postgraduate students in microeconomic analysis, economic theory and political economy. Robert P. Gilles is Professor of Economics at Queen's University Belfast, UK. He has previously taught in the USA and the Netherlands. His research focuses on the economic theory of the social division of labour.